Atomic Layer Deposition (ALD) of Alumina over Activated Carbon Electrodes Enabling a Stable 4 V Supercapacitor Operation. Issue 4 (15th February 2021) - Gandla, Dayakar; Song, Guanghui; Wu, Chongrui; Ein‐Eli, Yair; Tan, Daniel Q.
Abstract: Designing high voltage (>3 V) and stable electrochemical supercapacitors with low self‐discharge is desirable for the applications in modern electronic devices. This work demonstrates a 4 V symmetric supercapacitor with stabilized cycling performance through atomic layer deposition (ALD) of alumina (Al2 O3 ) on the surface of activated carbon (AC). The 20‐cycle ALD Al2 O3 coated AC delivers 84 % capacitance retention after 1000 charge/discharge cycles under 4 V, contrary to the bare AC cells having only 48 % retention. The extended cycling life is associated with the thickened Stern layer and suppressed oxygen functional group. The self‐discharge data also show that the Al2 O3 coating enables AC cells to maintain 53 % of charge retention after 12 h, which is more than twice higher than that of bare AC cells under the same test protocol of 4 V charging. The curve fitting analysis reveals that ALD coating induced slow self‐discharge dominated by ion diffusion mechanism, thus enhancing the AC surface energy. Abstract : 4 V symmetric supercapacitors are stabilized through optimizing Atomic Layer Deposition of Al2 O3 on activated carbon electrodes. The thickened Stern layer and suppressed oxygen functional group extend the cycling life at 4 V. The additional aluminum oxide layer enhances the energy barrier for ion desorption, thereby resulting in a decreased rate of self‐discharge. Too thick oxide coating blocks the nanopores and lower the cycling performance.